Arab Muslim Characters in Khadra’s Novel the Sirens of Baghdad - Naem , Dr. Ali Dakhil Naem (Thi Qar Arts Journal, 2023)
In this study, the researcher presented the American’s views of Islam and Muslims in Khadra’s Novel The Sirens of Baghdad. The image of Arab Muslim character is portrayed differently by the post-colonial novelists post September attacks 2001 on the World Trade Centre towers situated in New York City, USA. Since the accident, many American writers who represent the Western values have endeavored to stigmatize the picture of Arab Muslims through their writings using variant depictions to confirm their ‘Others’ as they consider the Arab Muslims their foes in the world. Consequently, the American writers perpetuate their previous negative picture to continue their domination upon the Arab Muslims, using post-colonial concepts in their portrayal. In contrast, the Arab writers try their best to depict the image of the Arab Muslim characters fairly as they have realistically witnessed and experienced the actual life events. Due to this, Orientalism, stereotyping, otherness and racism are the key concepts examined in this study related the Sirens of Baghdad. As many other Western and Arab writers have dealt with the same concepts previously, the current study examined and identified the concepts differently through this study concerning Arab Muslim characters from contrasting perspectives. Accordingly, the researcher adapted Said’s Orientalism theory as a main method of analysis. The research findings revealed that the American novelists purposely reflected dark aspects of the Arab Muslim characters so as to show to the world that Islam is a religion that propagates oppression and violence. On the other hand, the Arab novelists successfully and realistically proved that it is the Westerners who most of the time oppress the Arab Muslims and murder a fairly good number of them on the basis of false and unfounded allegations. As a conclusion, the study proposes a framework of the portrayal of the Arab Muslim characters conceptualized by the post-colonial perspective. It is recommended that future research examines the reliability and authentication of the respective American novels that have distorted the Arab Muslim identity by using high level of fictitious representations that is very distant from reality and truth, so that the negative representations of the Arab Muslim characters can righteously be repudiated. Moreover, future research can explore cross-cultural studies related to the novel concerned and the like of them so as to highlight the psychological, cultural and societal representations of the two nations—the Arab and the Western.